Role of lymphadenectomy in advanced-stage ovarian cancer: a meta-analysis - Ronsini, Carlo; Pasanisi, Francesca; Andreoli, Giada; De Franciscis, Pasquale; Cobellis, Luigi; Vizzielli, Giuseppe; Restaino, Stefano; Romeo, Paola; Palmara, Vittorio; Cianci, Stefano (Frontiers in Surgery, 2024)
BackgroundEpithelial Ovarian Cancer is one of the most lethal cancers among gynecologic malignancies. The disease metastasizes mainly through the peritoneal spread in the abdomen and through the lymphatic system. Lymph node involvement is present in 48% up to 75% of cases of advanced-stage ovarian cancer (ASOC). In this context, the aim of our study is to analyze the current literature on the topic and to investigate survival outcomes in patients affected by advanced-stage ovarian cancer undergoing lymphadenectomy.MethodsFollowing the recommendations in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, we systematically searched the Pubmed and Scopus databases in June 2022 since the first publication. We made no limitations on the country. We included the studies containing disease-free survival (DFS) and Overall Survival (OS) data. Only comparative studies with a direct comparison between Lymphadenectomy and its avoidance were included for meta-analysis.Results18 studies fulfilled the inclusion criteria. The overall OS, DFS, and RR were comparable in the studies. 26965 patients were enrolled in the meta-analysis. Patients were analyzed concerning OS and DFS. Meta-analysis highlighted statistically significant higher OS than the lymphadenectomy group (RR 1.31 [95% CI 1.16–1.48] p < .00001), and no statistically different DFS RR 1.23 [95% CI 0.82–1.92] p = 0.25).ConclusionOur analysis showed a protective role of lymphadenectomy in advanced ovarian cancer, with a reduction in death risk.Systematic Review Registration:www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022341646, Identifier CRD42022341646.